(untitled) (El-Wahat Journal for Research and Studies, 2025)
The Family Is Considered The Nucleus Of Society And The Basis Of Its Composition, And For This The Islamic Law Came With A Number Of Rulings To Enhance This Position And Highlight It, And Through This Research It Tries To Extract The Most Important Family Values Contained In Surat AL-Nur, Through The Extrapolation And Analysis The Quran. Through This Study, It Aims To Indicate The Impact Of These Values On The Child`S Raising And Upbringing, As The Child Is Considered An Element In The Family, And The Most Vulnerable To Internal And External Effects. Among The Most Important Results Reached: That The Primary Topic Of Surat AL-Nur Is To Preserve The Family Entity And Its Connection, And That It Has A Large Number Of Values That Were Not Mentioned In Other Fences, And These Values Have Affected The Child, Whether From His Social Or Moral Condition, Such As Preserving It From Loss And Preserving Its Position In Society, And Converting It With A Lot Of Morals, Such As Modesty, Honesty, And Courage. Key Words: Family Values, Surat AL-Nur, The Child.